Digenean trematodes from halfbeaks and needlefishes of Japan and adjacent waters - Machida, M. & Kuramochi, T. (Bulletin of the National Science Museum. Series A Zoology, 2000)
Thirteen species of digenean trematodes are recorded from halfbeaks and needlefishes of Japan and adjacent waters. One new genus and three new species are named: Hyporhamphitrema kamegaii gen. & sp. nov. from Hyporhamphus dussumieri of Japan, Bivesiculoides triangularis sp. nov. (Bivesiculidae) from Hyporhamphus quoyi of the Philippines and Brachyenteron japonicum sp. nov. (Zoogonidae) from Hemiramphus sajori of Japan. Hyporhamphitrema differs from the related waretrematids by having a simple type of hermaphroditic sac which includes a hermaphroditic duct and distal ends of male and female ducts. A new family Hyporhamphitrematidae is proposed for Hyporhamphitrema. The following taxonomic changes are proposed: Bucephalopsis southwelli Nagaty, 1937, B. lenti Nagaty, 1937, B. magnacetabulus Nagaty, 1937, B. tylosuris Ozaki & Ozaki, 1952, B. obpyriformis Gu & Shen, 1976, B. ablennus Gu & Shen, 1976 and B. bennetti (Hopkins & Sparks, 1958) of Gu & Shen, 1976, all from needlefishes, are synonymous with B. karvei Bhalerao, 1937.